2001
DOI: 10.1063/1.1377885
|View full text |Cite
|
Sign up to set email alerts
|

Sticking of HCl to ice at hyperthermal energies: Dependence on incidence energy, incidence angle, and surface temperature

Abstract: Articles you may be interested inElectron hole pair mediated vibrational excitation in CO scattering from Au(111): Incidence energy and surface temperature dependenceWe present calculations on the sticking of hyperthermal HCl to the basal plane ͑0001͒ face of ice I h at normal and off-normal incidence. The dependence of the sticking probability on the incidence energy (E i ), the angle of incidence ( i ), and the surface temperature (T s ) is discussed. Two sticking mechanisms are observed. For i р30°, penetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
46
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 65 publications
11
46
1
Order By: Relevance
“…34 -41 Those calculations showed that the scattering probability of HCl and CO increases with the incidence energy 36,37 and the incidence angle. 35,37 For off-normal incidence, the hotter HCl and CO molecules scatter at larger angles, 35,37 in agreement with the results obtained from molecular beam experiments on the scattering of Ar atoms and HCl molecules from crystalline ice at hyperthermal energies. 26,27 The energy transfer from the impinging atom 34 or molecule 36,37 to the ice and the energy dissipation within the ice surface were found to be fast and efficient: most of the incidence energy is transferred to the surface in the first bounce and the energy dissipation occurs within 0.5 ps.…”
Section: Introductionsupporting
confidence: 83%
“…34 -41 Those calculations showed that the scattering probability of HCl and CO increases with the incidence energy 36,37 and the incidence angle. 35,37 For off-normal incidence, the hotter HCl and CO molecules scatter at larger angles, 35,37 in agreement with the results obtained from molecular beam experiments on the scattering of Ar atoms and HCl molecules from crystalline ice at hyperthermal energies. 26,27 The energy transfer from the impinging atom 34 or molecule 36,37 to the ice and the energy dissipation within the ice surface were found to be fast and efficient: most of the incidence energy is transferred to the surface in the first bounce and the energy dissipation occurs within 0.5 ps.…”
Section: Introductionsupporting
confidence: 83%
“…Essentially, we followed the same approach as used previously to study the adsorption of HCl and CO to crystalline and amorphous ice at thermal and hyperthermal energies, where E i varies between 0.1 and 2.0 eV (Kroes & Clary 1992;Al-Halabi et al 2001.…”
Section: Methodsmentioning
confidence: 99%
“…The H atom photodesorption probabilities are larger than those for D in the H 2 O and D 2 O amorphous ice systems ( 39,40 states that the energy transfer from the X atom to a water molecule (which is assumed to be stationary initially) is dependent on the mass ratio of the two colliding objects, as follows:…”
Section: A X(=hd) Atom Photodesorptionmentioning
confidence: 99%